Dialetti italiani “esportati” nell’Ottocento tra Europa meridionale e Mediterraneo: Per una mappatura delle sopravvivenze comunitarie e delle eredità - Toso, Fiorenzo (Verbum – Analecta Neolatina, 2008)
This paper examines the historical events and the linguistic consequences of a number of migratory movements from Italy to Southern European and Mediterranean countries between the end of the 17th century and the first few decades of the 18th century. Such directions and destinations are lesser known than those migrations generally associated "historically" with Italian emigration (North and South America, and, more recently, Northern Europe and Australia); nevertheless, the linguistic heritage of such movements is still very much alive or else has become extinct in only very recent times. Those who migrated from Veneto and Trentino to the Balcans, from Puglia to Crimea, the Sicilians who emigrated to Tunisia, the Piedmontese who went to province, the Ligurians who moved to various locations from Gibraltar to the Black Sea, all gave birth to small linguistic communities, to real dialectal koinès, to important phenomena of mixing codes and lexical borrowing from the local languages. An overall picture will be built up in order to evaluate the importance of these phenomena and to posit a series of hypotheses of a sociolinguistic and political nature.